2005
DOI: 10.1080/00016480510039003
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic resection of pleomorphic adenoma arising in the nasopharynx

Abstract: Pleomorphic adenoma is the commonest benign tumor of the salivary glands. It has rarely been reported arising in the nasopharynx. A pleomorphic adenoma originating from the left lateral wall of the nasopharynx was found in a 61-year-old female who presented with nasal obstruction and intermittent epistaxis. It was successfully removed by combined transnasal and transoral surgery under endoscopic visualization. Endoscope-guided surgery may be helpful for the complete resection of benign nasopharyngeal tumors wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 10 publications
1
23
0
Order By: Relevance
“…Moreover, once the lesion pedicle was identified, endoscopic-assisted surgery permitted us a minimal invasive excisional biopsy. As also reported by Roh et al [8], even in our experience we confirm that endoscopic surgery is effective to obtain the complete resection of benign nasopharyngeal tumors thus achieving surgical clear margins of resection with a low risk of injuries to the Eustachian tube. …”
Section: Discussionsupporting
confidence: 90%
“…Moreover, once the lesion pedicle was identified, endoscopic-assisted surgery permitted us a minimal invasive excisional biopsy. As also reported by Roh et al [8], even in our experience we confirm that endoscopic surgery is effective to obtain the complete resection of benign nasopharyngeal tumors thus achieving surgical clear margins of resection with a low risk of injuries to the Eustachian tube. …”
Section: Discussionsupporting
confidence: 90%
“…An extensive literature review revealed only nine cases of PA arising in the nasopharynx [6,[10][11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Roh et al . [20] excised a pleomorphic adenoma of nasopharynx in a 61-year-old female by endoscope. They advocated use of endoscope in these cases to avoid injury to eustachian tube.…”
Section: Discussionmentioning
confidence: 99%